2005
DOI: 10.1038/sj.ejhg.5201403
|View full text |Cite
|
Sign up to set email alerts
|

Association of DLG5 R30Q variant with inflammatory bowel disease

Abstract: Crohn's disease (CD) and ulcerative colitis (UC) are chronic inflammatory diseases of the gastrointestinal system known as the inflammatory bowel diseases (IBD). Recently, Stoll and colleagues reported a novel finding of genetic variation in the DLG5 gene that is associated with IBD (CD and UC combined). We present here a study of the genetic variation described in that report in two well-powered, independent case-control cohorts and one family-based collection, and confirm the proposed association between IBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 14 publications
1
47
0
Order By: Relevance
“…Meanwhile, replication studies have emerged, but results are conflicting. Whereas Daly et al 47 was able to show independent replication in two cohorts from Quebec/ Italy and Quebec/UK, other recent studies were not able to show association. [48][49][50] More studies are inevitably needed to understand more about this gene.…”
Section: Current Status Of Genetics Research In Ibd S Vermeire and P mentioning
confidence: 79%
“…Meanwhile, replication studies have emerged, but results are conflicting. Whereas Daly et al 47 was able to show independent replication in two cohorts from Quebec/ Italy and Quebec/UK, other recent studies were not able to show association. [48][49][50] More studies are inevitably needed to understand more about this gene.…”
Section: Current Status Of Genetics Research In Ibd S Vermeire and P mentioning
confidence: 79%
“…The association of the R30Q variant with IBD has been supported in some studies [12,24,25,27], but failed to be replicated in others [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Stoll et al, [12] identified an IBD risk-associated DLG5 haplotype D that is uniquely distinguished by the 113A variant of R30Q. The association of R30Q with IBD has been replicated in other studies from several different patient populations [24][25][26]. Friedrichs et al, found a male-specific association of the R30Q variant with CD, with no association of the R30Q variant with women, nor with the entire sample of men and women [27].…”
Section: Introductionmentioning
confidence: 94%
“…Present approaches have not been able to discern whether these other genes or the class â…ˇ genes are the true risk genes in the HLA locus. [79][80][81][82] , multiple polymorphisms in the MDR1/ABCB1 gene on chromosome 7q [83][84][85][86][87][88][89][90][91][92] , and polymorphisms in the DLG5 gene on chromosome 10q [70,[93][94][95][96][97][98][99][100][101][102] . (See section C.4.1.)…”
Section: Hla Associationsmentioning
confidence: 99%